Bio-interventional uveoscleral outflow enhancement in patients with medically uncontrolled primary open-angle glaucoma: 1-year results of allograft-reinforced cyclodialysis - Kevin Barber; Brian Flowers; Michael Patterson; Lautaro Vera; Tsontcho Ianchulev; Iqbal Ike Ahmed (Therapeutic Advances in Ophthalmology)
Background: Scleral allograft-reinforced cyclodialysis intervention can achieve sustained intraocular pressure (IOP) reduction by enhancing uveoscleral outflow in hypertensive patients with primary open-angle glaucoma (POAG) failing medical therapy. Objectives: To evaluate clinical outcomes of bio-interventional uveoscleral outflow enhancement surgery through 12 months of follow-up in POAG subjects who are inadequate responders to IOP-lowering medical treatment. Design: Prospective interventional real-world evidence trial. Methods: Patients with POAG and medicated baseline IOP >21 mmHg failing medical therapy underwent bio-interventional uveoscleral outflow enhancement surgery with an ab-interno allograft-reinforced cyclodialysis. Acellular allogeneic scleral bio-tissue was micro-trephined, shaped, and loaded in a delivery cannula for internal scaffolding. Endoscleral reinforcement of the cyclodialysis was then performed to maintain the internal uveoscleral filtration conduit. Effectiveness outcomes such as IOP and IOP-lowering medication use, as well as ocular safety and tolerability, were analyzed through 12 months post-op. Results: Fifty-one eyes were enrolled with a baseline medicated IOP greater than 21 mmHg. The average age was 70.9 ± 8.5. The mean best corrected visual acuity (BCVA) at baseline was 0.40 ± 0.32, and the mean medicated IOP was 25.7 ± 4.4 mmHg on 1.2 ± 1.3 IOP-lowering medications. In 83% of cases, visually significant cataract comorbidity was present and treated with adjunct phacoemulsification. The bio-interventional cyclodialysis surgery and scleral reinforcement were successfully performed in all cases. The procedures were well tolerated, and there were no visually significant or serious, vision-threatening ocular adverse events. Durable and sustained reinforcement of the cyclodialysis was achieved through 12 months of follow-up without migration, displacement, or attrition of the allograft bio-scaffold. At 12 months post-op, there was a statistically significant ( p  < 0.01) and sustained reduction in IOP from 25.7 + 4.4 mmHg at baseline down to 15.4 ± 4.5 mmHg, with a concurrent 42% reduction in IOP-lowering medications. 86.7% of subjects achieved a medicated IOP <18 mmHg while on fewer or the same number of IOP-lowering medications. Conclusion: Uveoscleral outflow enhancement can be surgically enhanced in an ab-interno approach through bio-interventional cyclodialysis with adjunct scleral allograft reinforcement to lower IOP in open-angle glaucoma patients who are inadequate responders to medical therapy. Trial registration: The study was registered with clinicaltrials.gov NCT05506423.